Web-based Inventory System at 24PROJECT Using the Design Thinking Method - Agung Syahputra, Wili Agung Syahputra; Andhika Putri, Nadya; Hendry, Hendry (Bahasa Indonesia, 2025)
An effective inventory management system is essential for companies to ensure the availability and accuracy of goods data. 24PROJECT previously used a manual recording method that caused various problems, such as data discrepancies, reporting delays, and potential human error. To overcome these problems, this research aims to design and develop a web-based inventory information system with a Design Thinking approach that focuses on user needs and convenience. The development process is carried out through stages: problem identification, goal setting, literature study, data collection, system analysis, interface design, and system testing. The technologies used in the implementation of this system are Dart, Flutter, and Pocketbase. The results of the research show that the system built is able to record and monitor goods transactions in real-time, present stock and transaction reports accurately, and improve work efficiency and decision making. With a simple, informative, and easy-to-use interface, this system successfully provides an adaptive and effective digital solution for inventory management at 24PROJECT.